(untitled) (Hoboken, N.J., 2007)
Nanoscale: Issues and Perspectives for the Nano Century addresses the emerging ethical, legal, policy, business, and social issues. A compilation of provocative treatises, this reference: Covers an area of increasing research and funding; Organizes topics in four sections: Policy and Perspectives; Nano Law and Regulation; Nanomedicine, Ethics, and the Human Condition; and Nano and Society: The NELSI Imperative; Presents differing perspectives, with views from nanotechnology's most ardent supporters as well as its most vocal critics; Includes contributions from professionals in a variety of industries and disciplines, including science, law, ethics, business, health and safety, government regulation, and policy.
Keywords: Nanotechnology,Nanotechnology; Moral and ethical aspects,Social aspects